Semantically congruent bimodal presentation modulates cognitive control over attentional guidance by working memory. - Cai, Biye; Tang, Xiaoyu; Wang, Aijun; Zhang, Ming (Memory & Cognition, 2024)
Although previous studies have well established that audiovisual enhancement has a promoting effect on working memory and selective attention, there remains an open question about the influence of audiovisual enhancement on attentional guidance by working memory. To address this issue, the present study adopted a dual-task paradigm that combines a working memory task and a visual search task, in which the content of working memory was presented in audiovisual or visual modalities. Given the importance of search speed in memory-driven attentional suppression, we divided participants into two groups based on their reaction time (RT) in neutral trials and examined whether audiovisual enhancement in attentional suppression was modulated by search speed. The results showed that the slow search group exhibited a robust memory-driven attentional suppression effect, and the suppression effect started earlier and its magnitude was greater in the audiovisual condition than in the visual-only condition. However, among the faster search group, the suppression effect only occurred in the trials with longer RTs in the visual-only condition, and its temporal dynamics were selectively improved in the audiovisual condition. Furthermore, audiovisual enhancement of memory-driven attention evolved over time. These findings suggest that semantically congruent bimodal presentation can progressively facilitate the strength and temporal dynamics of memory-driven attentional suppression, and that search speed plays an important role in this process. This may be due to a synergistic effect between multisensory working memory representation and top-down suppression mechanism. The present study demonstrates the flexible role of audiovisual enhancement on cognitive control over memory-driven attention.